Pengaruh Suhu dan Waktu Pirolisis terhadap Karakteristik Arang dari Tempurung Kelapa - Hasibuan, Rosdanelli; Pardede, Hans Martua (Talenta Publisher (Universitas Sumatera Utara), 2023)
The increased production of coconut has increased by the shell produced, even though this coconut shell has lignin content of 33.30% so it has the potential to be converted into charcoal through the pyrolysis process. Pyrolysis is a thermal decomposition process that occurs without air or with little air to convert biomass into charcoal. Coconut shell charcoal can be used for coal co-firing in developing new and renewable energy. This study aimed to obtain the best pyrolysis temperature and time in the manufacture of high-calorific value coconut shell charcoal in accordance with SNI 06-4369-1996. Coconut shell pyrolysis was carried out at temperatures of 350 °C, 450 °C and 550 °C and pyrolysis times of 2 hours, 3 hours and 4 hours. The results showed that charcoal with the highest calorific value was produced at a temperature of 450 °C and a pyrolysis time of 3 hours. The resulting charcoal had calorific value of 7,750.96 cal/g, yield of 30.10%, and contained 2.75% water, 2.70% ash and 9.50% volatile matter.